Front cover: Protein markers of Bursaphelenchus xylophilus Steiner & Buhrer, 1934 (Nickle, 1970) populations using quantitative proteomics and character compatibility. Issue 6 (March 2016) - Ciordia, Sergio; Robertson, Lee; Arcos, Susana C.; González, María Rosa; Mena, María del Carmen; Zamora, Paula; Vieira, Paulo; Abrantes, Isabel; Mota, Manuel; Castagnone‐Sereno, Philippe; Navas, Alfonso
Abstract : DOI:10.1002/pmic.201500106 The cover design represents the importance of quantitative proteomics (iTRAQ) and Character Compatibility Analysis as robust criteria for biomarker selection, through conversion of quantitative to binary values by application of contrasted statistics. We have applied it to connect hierarchically several populations of the European quarantine pinewood nematode ( Bursaphelenchus xylophilus ). For more details see the article by Sergio Ciordia et al. on page 1006.